Tingkatkan Daya Saing UMKM Melalui Sosialisasi Digital Marketing bagi Pelaku UMKM di Kelurahan Kramat Selatan - Dheva Febriyanti Purwanto; Novita Nur Azizah; Nurul Laila; Mila Dianur Sabilla; Salwa Nabilla; Joko Tri Nugraha (Institut Teknologi dan Bisnis Semarang, 2024)
Digital marketing is one of the main keys to increasing the competitiveness of business actors, especially micro, small, and medium enterprises (MSMEs). However, the main challenge that is often faced in digital marketing is that many business actors do not yet have an understanding of the use and application of digital marketing. To overcome this problem, Tidar University KKN students carried out socialization activities at Hall RW. At the survey stage, visits were made to each MSME location. The stages of implementing socialization were carried out by bringing in speakers from the Magelang Mayor's Expert Team. The final stage is follow-up visits to each MSME location. The final aim of this activity is to provide further assistance that ensures the application of the knowledge that has been provided during socialization. By making repeat visits to MSME locations, the community service team can help business actors practice the digital marketing techniques they have learned.